The Effect of Nostalgia Proneness on Ad-Evoked Nostalgia, Brand Attitude and Purchase Intention - Şeniz Özhan (Istanbul Business Research (IBR), 2020)
Nostalgia is generally defined as a longing for the past, and from a marketing perspective it can be described as an emotion that drives the purchase behaviors of consumers. Companies have started to make use of the element of nostalgia in their marketing strategies more frequently in order to be more successful than their competitors in today's intensely competitive market. The aim of the study is to examine the effect of nostalgia proneness on ad-evoked nostalgia, attitude and purchase intention as well as to evaluate it with regard to the purchase decision making process of the consumer. The structural equation model was used for testing the developed hypothesis with a sample group comprised of 381 consumers. The study puts forth that sense of nostalgia has a strong effect on ad-evoked nostalgia, attitude and purchase intention. The findings of the study point out to the marketers that nostalgic signs in advertisements may have positive effects on the brand attitude and the purchase intention of the targeted groups.
Keywords: 650; Nostalgia Proneness; Nostalgic Advertisements; Ad-evoked Nostalgia; Brand Attitude; Purchase Intention